MACROZOOBENTHOS COMMUNITY STRUCTURE IN THE INTERTIDAL ZONE OF MUARA AIR HAJI VILLAGE PESISIR SELATAN REGENCY WEST SUMATERA PROVINCE - Alhadad, Ilham; Tanjung, Afrizal; Zulkifli, Zulkifli (Asian Journal of Aquatic Sciences, 2024)
Muara Air Haji Village is a coastal area with various anthropogenic activities that can disrupt the aquatic ecology, especially in the intertidal zone. Biological indicators such as macrozoobenthos are needed to provide a correct and sustainable picture of water quality. This research uses a survey method to determine macrozoobenthos' type, abundance, diversity, uniformity, dominance, and distribution pattern in the intertidal zone. Sampling was carried out using three stations, and each station consisted of three transects and three subzones comprised of the upper, middle, and lower intertidal zones using a quadrant plot measuring 1 x 1 m. The results of this research found three classes of macrozoobenthos with five species. Abundance values ​​at each station ranged from 0.89–4.56 ind/m2, while abundance in the intertidal subzone ranged from 1.11–3.56 ind/m2. The diversity index (H') at stations I and III is 1.93 and 1.17, which means it is included in the medium diversity category, while the diversity index (H') at station II is 0.84, which means it is included in the low category, moderate distribution of individuals or non-uniform number of individuals, moderate ecological pressure and moderately polluted water stability. The uniformity index value ranges from 0.65–0.99, which means the uniformity category is balanced. At station II, macrozoobenton dominates with an index value of 0.62, while stations I and III have no dominant species with index values ​​of 0.30 and 0.45. The distribution pattern (Id) of macrozoobenthos is clustered with a value of 3.45–4.18.